Effects of repeated intragastric administrations with heat-inactivated Mycobacterium aurum DSM 33539 on the stress-induced aggravation of dextran sulfate sodium (DSS) colitis in C57BL/6N mice - Langgartner, Dominik; Weiss, Anna-Lena J.; Amoroso, Mattia; Sterrett, John D.; Lowry, Christopher A.; Reber, Stefan O. (Frontiers in Neuroscience, 2025)
Stress-protective effects have been reported for M. vaccae NCTC 11659 and M. vaccae ATCC 15483T. However, it remains to be investigated whether also closely related rapidly growing environmental saprophytic non-tuberculous mycobacteria (NTM) species have protective effects against the negative consequences of chronic psychosocial stress. Therefore, the aim of the current study was to assess whether repeated i.g. administrations of a heat-inactivated preparation of Mycobacterium aurum DSM 33539 prior to 19 days of chronic subordinate colony housing (CSC) are able to ameliorate the negative effects of this preclinically validated mouse model for chronic psychosocial stress on subsequent dextran sulfate sodium (DSS) colitis in male C57BL/6N mice. The results of the present study show that repeated i.g. administrations of M. aurum DSM 33539 have stabilizing effects on the composition of the gut microbiome, indicated by the findings that M. aurum DSM 33539 prevented CSC-induced increases in the relative abundances of the colitogenic phyla Desulfobacterota and Deferribacterota. Indeed, the relative abundance of Deferribacterota on day 19 was strongly correlated with histological damage to the colon. In line with the latter, M. aurum DSM 33539 was further protective against the aggravating effects of stress on subsequent DSS colitis. Collectively, our findings confirm and extend previous findings from our group and suggest that the stress-protective effects reported for M. vaccae NCTC 11659 and M. vaccae ATCC 15483T are generalizable also to other NTM species.